Optimal PIDA Controller Design for Maglev Vehicle Suspension System by Lévy-Flight Firefly Algorithm: - - Puangdownreong, Deacha (Srinakharinwirot University Engineering Journal, 2019)
In modern vehicles, intelligent suspension systems have been widely applied with complex control algorithms. The suspension design problem aims to achieve a good suspension providing a comfortable ride and good handling within a reasonable range of road-profile deflection. In this paper, the proportional-integral-derivative-accelerated (PIDA) controller design for the magnetically levitated (Maglev) vehicle suspension system by the Lévy-flight firefly algorithm (LFFA), one of the most powerful metaheuristic optimization searching techniques, is proposed. For comparison with LFFA-based design approach, the results obtained by the PIDA controller will be compared with those obtained by the PI, PD and PID controllers. Simulation results show that the LFFA can provide optimal PIDA controller for a given suspension system. The PIDA controller yielded very satisfactory response superior to PI, PD and PID, respectively.